Do smoking habits differ between women and men in contemporary Western populations?: evidence from half a million people in the UK Biobank study - Peters, S.; Huxley, Rachel; Woodward, M. (2015)
Objectives: Several studies have shown that smoking may confer a greater excess risk for chronic diseases in women compared with men. The reasons for this excess risk of smoking in women are unclear, yet sex differences in smoking habits may play a role. We, thus, characterised sex differences in smoking habits in a contemporary Western population. Design: Cross-sectional population-based study. Setting: UK Biobank Resource. Participants: 499 797 (54% women) individuals with data on smoking habits. Main outcome measures: Women-to-men prevalence ratios in smoking status, and the women-minus-men mean difference in age at smoking initiation, number of cigarettes smoked daily and age at smoking cessation in 5-year birth cohort bands. Results: The women-to-men ever-smoking ratio ranged from 0.57 in the oldest to 0.87 in the youngest birth cohort. In the oldest cohort, born 1935-1939, women started smoking 1.9 years (95% CI 1.7 to 2.1) later than did men, but in those born after 1959 there was no difference in the age at initiation. The oldest women smoked 5.3 (95% CI 4.7 to 5.9) cigarettes per day fewer than did the oldest men, compared with 2.0 (95% CI 1.7 to 2.3) fewer cigarettes smoked per day in the youngest, born 1965 -1969. Among quitters, women born before 1945 were, on average, 1.5 years older than their male contemporaries, but this differential was 1 year or less among people born after 1949. Conclusions: Differences in smoking behaviour between women and men have decreased over time. Even past differentials are unlikely to explain the increased susceptibility to smoking-related chronic disease in women compared with men that has previously been observed. Future studies are required to determine whether sex differences in the physiological and biological effects of smoking are responsible for the differential impact of smoking on health in women and men.